The Shape of Water: Analysis of Corporate Water Disclosure in Indonesia - Desi Adhariani (Australasian Accounting, Business and Finance Journal, 2021)
Indonesia is facing a water crisis in terms of the scarcity and quality of its water resources. Considering this water-constrained future, it is important that several parties, including companies in Indonesia as one of the significant actors, pay attention to the pristine management and reporting of this scarce resource. This study evaluates the reporting and disclosure requirements of water of Indonesian listed companies in 2014 - 2016. Content analysis was used as the research method to analyse the water disclosure and to evaluate the adequacy of the disclosure against the global disclosure requirement from the Global Reporting Initiative (GRI) G4. The findings of the study show that most of the companies have illustrated the commitment toward water stewardship by reporting on water-related aspects. However, when compared to the global standard, the level of disclosure is still low, which might reflect the lack of demand from stakeholders or the low necessity to seek legitimacy from water reporting. This also implies future opportunities for companies to better perform water management and present a more complete water disclosure for stakeholders.
Keywords: water reporting; water management; accountability; Indonesia; GRI